Sistematic review of subfamily Phryninae (Arachnida: Amblypygi) - Joya, Daniel Andres Chirivi (2018)
The subfamily Phryninae (Arachnida: Amblypygi) has not been recently revised, which causes many difficulties for species identification. Thus far, no phylogenetic hypothesis has been proposed for this subfamily. The nomenclature of diagnostic characters is not uniform, and most illustrations are poorly detailed. We reviewed the subfamily Phryninae, redescribed all known species, and described six new species. We proposed a unified nomenclature for teeth of chelicerae and pedipalpal spines. We performed a phylogenetic analysis using total evidence and direct optimization in the program POY. We built a morphological matrix of 92 terminals and 174 characters, and a molecular matrix with 1557 pb (markers COl, 12s and 16s). Both sets of information were analyzed separately to understand their influence over the total evidence analysis. The results of the three analyses were different: the morphological analysis did not recover the subfamily Phryninae as monophyletic, this analysis produced 90 equally parsimonious topologies, however, the strict concensus tree had good resolution. The molecular analysis did not recover the family Phrynidae as monophyletic, but Phryninae was recovered. Total evidence analysis allowed for obtain just one more parsimonious hypothesis which included all species of Phrynidae, and resolved the politomies obtained with the analysis using morphology only, in this hypothesis Phrynidae and its subfamilies are monophyletic. ln all results, the genera of Phryninae were polyphyletic. We selected the tree of total evidence analysis to build a new taxonomic proposal, we decided to keep Acanthophrynus, Phrynus, and Paraphrynus and to create five new genera: Caicedophrynus gen. nov., Cronopiophrynus gen. nov., Gabophrynus gen. nov., Gentiloprynus gen. nov., Girondophrynus gen. novo Accordingly, we proposed 44 nomenclatural changes. Our results showed that the diversity of this group could be greater, therefore, we highlight that populational and phylogeographic studies of Phryninae are important